A new hyper-thermostable carboxylesterase from Anoxybacillus geothermalis D9 - Mohd Johan, Ummie Umaiera; Raja Abd. Rahman, Raja Noor Zaliha; Ahmad Kamarudin, Nor Hafizah; Latip, Wahhida; Mohamad Ali, Mohd Shukuri (Elsevier, 2022)
Carboxylesterases are attractive biocatalysts for various industrial applications, especially hyperthermophilic carboxylesterases, due to their high tolerance toward extreme environments. Such ability confers many advantages, including cost-effectiveness and an increased manufacturing rate. In the current work, we first described the characterization of EstD9, a new carboxylesterase from thermophilic Anoxybacillus geothermalis D9. Sequence analysis of EstD9 revealed a significant identity (80 %) with thermophilic Est30 and a catalytic triad, composed of Ser93-His22-Asp193. As the protein sequence contained a conserved pentapeptide (GLSLG), EstD9 could be proposed as a new member of family XIII. The putative carboxylesterase was recombinantly expressed in E. coli BL21 (DE3) with a molecular mass of 28 kDa and successfully purified via affinity chromatography with recovery of 88.36 %. Using p-nitrophenyl butyrate, EstD9 presented excellent stability at high temperature range (70 °C–100 °C) and a broad pH tolerance (pH 6–9), with optimal activity at 80 °C and pH 7. Notably, EstD9 activity was stimulated in the presence of 1-propanol and DMSO with 107.8 % and 108.9 % relative activities, respectively. The purified EstD9 maintained 60 % residual activity after 30 min exposure to various surfactants and metal ions. Additionally, the inhibition studies demonstrated strong deactivation by phenylmethylsulfonyl fluoride, dithiothreitol, and β-mercaptoethanol. The estimated Tm value was 72.12 °C. Unlike typical carboxylesterases, in silico 3D model of EstD9 disclosed a topological α/β hydrolase fold with a small α-helix cap. The enzymatic properties of EstD9 suggest this enzyme to be a highly suitable catalyst for industrial bioprocesses under harsh conditions.